Sistema web de gestión administrativa en el departamento de tesorería del cuerpo de bomberos “Casimiro farfán” del cantón Bolívar - Carranza Basurto, Eliana Elizabeth (2013)
With the goal to the delivery process in order to give the certificate in the Treasury Fire station Department "CasimiroFarfán" Calceta City, Canton Bolívar, was created and implemented a computer system, for this purpose an evaluation, which determined that the processes carried out within that establishment, greater speed and accuracy required when making information searchable, generate statistical reports, among other activities. In the creation of the computer application made use of tools and techniques for developing next generation software, such as process flow diagram (PFD), using the Model UWE and Microsoft Visual Basic 2010 language. The installation and commissioning of the application, along with an interview with Mr. Johnny Zambrano treasury department manager allowed to validate the software, obtaining satisfactory results as reducing time and physical document recording processes of the main features customer.